2004
DOI: 10.1002/ijc.20019
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer mortality patterns in selected Central, Eastern and Southern European countries

Abstract: Significant changes in the prevalence of tobacco smoking have been observed in many European countries. EU candidate countries have also experienced major changes with respect to tobacco smoking, which have resulted in changes in the frequency of lung cancer. In men in the majority of these countries, a reduction of mortality rates has been observed recently, while in Hungary and Poland a deceleration of mortality increase was observed in the 1990s. The situation is much less favorable in females, where in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 32 publications
(67 reference statements)
2
39
0
4
Order By: Relevance
“…However, as shown in Table 1, the ratio of early-to-late onset PC varies widely across countries. An excess of EOPC is seen in Central/ Eastern European countries-an area with high smoking prevalence rates (7). In this region, the proportion of YPLL from EOPC could represent as much as one-third of the total mortality burden from PC.…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown in Table 1, the ratio of early-to-late onset PC varies widely across countries. An excess of EOPC is seen in Central/ Eastern European countries-an area with high smoking prevalence rates (7). In this region, the proportion of YPLL from EOPC could represent as much as one-third of the total mortality burden from PC.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, incidence and mortality are increasing rapidly in Southern and Eastern European countries. 23 In women, the epidemic is less advanced; most Western countries are still showing a rising trend in incidence and mortality, although in some this is recent and affecting only recent generations (Spain), while for others (United Kingdom), it seems that the peak of risk may now have been reached. 22,24 Breast Cancer Breast cancer is by far the most frequent cancer of women (23% of all cancers), with an estimated 1.15 million new cases in 2002, ranking second overall when both sexes are considered together.…”
Section: Lung Cancermentioning
confidence: 99%
“…Furthermore, as the tobacco epidemic among women occurred later than it did among men, it requires ongoing documentation as it continues to unfold. Previous studies have shown increasing lung cancer mortality among women in Europe, North America, Australia, New Zealand, and parts of Asia through the first decade of the 2000s with plateauing or decreasing rates achieved more recently in a few countries, particularly among younger women (7)(8)(9)(10)(11)(12). Increasing rates have also been reported in Latin America through 2000 (13).…”
Section: Introductionmentioning
confidence: 99%